Safety and pharmacokinetics of veliparib extended‐release in patients with advanced solid tumors: a phase I study. (7th May 2018) - Werner, Theresa L.; Sachdev, Jasgit; Swisher, Elizabeth M.; Gutierrez, Martin; Kittaneh, Muaiad; Stein, Mark N.; Xiong, Hao; Dunbar, Martin; Sullivan, Danielle; Komarnitsky, Philip; McKee, Mark; Tan, Antoinette R.
Abstract: The poly(ADP‐ribose) polymerase‐1/2 inhibitor veliparib is active against tumors deficient in homologous DNA damage repair. The pharmacokinetics and safety of veliparib extended‐release (ER) were evaluated in patients with advanced solid tumors. This phase I study assessed veliparib‐ER up to 800 mg once daily or 600 mg twice daily. Dose‐limiting toxicities (DLTs), recommended phase II dose (RP2D), and maximum tolerated dose (MTD) were assessed in cycle 1 and safety/tolerability during continuous administration (28‐day cycles). Seventy‐one patients ( n  = 53 ovarian, n  = 17 breast, n  = 1 prostate carcinoma) received veliparib; 50 had deleterious breast cancer susceptibility ( BRCA) gene mutations. Single‐dose veliparib‐ER 200 mg (fasting) led to 58% lower peak concentration and similar area under the concentration‐time curve compared with veliparib immediate‐release (IR). Three patients experienced DLTs (grade 2: asthenia; grade 3: nausea/vomiting, seizure). RP2D and MTD for veliparib‐ER were 400 mg BID. The most frequent adverse events (AEs) were nausea (78.9%) and vomiting (50.7%). The most common grade 3/4 treatment‐related AEs were as follows: thrombocytopenia (7.0%), nausea, and anemia (4.2% each). Overall, 12 (27.3%) patients with ovarian and 10 (62.5%) patients with breast carcinoma had a partial response. Veliparib‐ER, versus veliparib‐IR, exhibited an improved pharmacokinetic profile and was well tolerated in patients with ovarian and BRCA ‐mutated breast cancers. Abstract : Veliparib is active against tumors deficient in homologous DNA damage repair. This phase I study assessed the pharmacokinetics and safety of veliparib extended‐release (ER) versus veliparib immediate‐release (IR) in patients with advanced solid tumors. Veliparib‐ER, versus veliparib‐IR, exhibited an improved pharmacokinetic profile and was well tolerated in patients with ovarian and breast cancer susceptibility gene‐mutated breast cancers.